2020
DOI: 10.1002/adma.202070077
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Gels: Mechanical Control of Periodic Precipitation in Stretchable Gels to Retrieve Information on Elastic Deformation and for the Complex Patterning of Matter (Adv. Mater. 10/2020)

Abstract: The direction, time, and duration of mechanical deformation on soft material can be tracked using reaction–diffusion systems. In article number 1905779, Bilge Baytekin and co‐workers show that, similar to the environmental changes affecting the final pattern of a tree's life rings, various mechanical inputs can lead to numerous different patterns in hydrogels, and these patterns can be used in complex patterning of material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Separating RGB components and converting them to corresponding absorbance values was also helpful in determining the widths (see Figure ) of the bands, which is otherwise not possible using the Gy-values. Our preliminary calculations on widths of the bands using half prominence (half of the difference between G of bands and their neighbor depletion zone) , showed that such calculation did not yield the correct widths as far as the systems described in the present work are concerned. It should also be noted that the observance of secondary structures can also be attributed to the compartmentalization of pixel information in RGB.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Separating RGB components and converting them to corresponding absorbance values was also helpful in determining the widths (see Figure ) of the bands, which is otherwise not possible using the Gy-values. Our preliminary calculations on widths of the bands using half prominence (half of the difference between G of bands and their neighbor depletion zone) , showed that such calculation did not yield the correct widths as far as the systems described in the present work are concerned. It should also be noted that the observance of secondary structures can also be attributed to the compartmentalization of pixel information in RGB.…”
Section: Resultsmentioning
confidence: 66%
“…Image analysis has been an important part of investigations on chemical pattern formation. A careful analysis of the literature indicated that the image analysis methods have specific roles, for example, Mandalian et al, Shreif et al, and Badr et al, employed image analysis particularly for the morphological analysis of precipitates formed in Liesegang patterns. However, recently, Morsali et al, , performed image analysis by extracting the data into ImageJ software, and in conjunction with MATLAB codes, the spatial analysis of the bands was done. Although the method is similar to that of the present work, the differences remain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, another recent study achieved this rate control and formation of equidistant-type LPs based on mechanical changes in morphology of a gel. 37 However, these methods required the application of external forces along with programming and executing during pattern formation. Therefore, these methods did not embody ideal pattern formation in RD systems consisting of only the programming−executing process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…LPs obeying this equation are known as regular-type LPs. However, exceptional equidistant- and revert-type LPs show a constant and monotonically decreasing Δ x n , respectively, with increasing x n ; thus, these LPs do not satisfy eq . Such patterns can exist individually, and in some cases, LP-like patterns in nature show complex periodicity because of the coexistence of the aforementioned types of LPs.…”
Section: Introductionmentioning
confidence: 99%